Rekognisi Sosio Historis Kewenangan Pengawasan BPD dalam Pemerintahan Desa Menurut Undang-Undang Desa Perspektif Siyasah Dusturiyah - Putri, Zulfa Listiani; Rizal, Lutfi Fahrul; Amin, Muhammad (STAIN MAJENE, 2025)
This study analyzes the legitimacy and supervisory function of the Village Consultative Body (Badan Permusyawaratan Desa/BPD) within the framework of village autonomy by linking historical evolution, the spirit of deliberation (musyawarah), and the legal maxim dar’u al-mafāsid muqaddamun ‘alā jalb al-maṣāliḥ. The BPD is understood as the product of an adat–state negotiation that evolved from pre-colonial village deliberative forums (rembug desa) that were organic and inclusive, weakened into subordinate meetings during the colonial period, formalized as the Village Consultative Council (LMD) after independence, and later transformed into the modern BPD (Law No. 22 of 1999 and Law No. 6 of 2014). Normatively, the BPD functions as a counterbalance to the executive; however, in practice it remains vulnerable to patronage and bureaucratization, causing its oversight role to be largely symbolic and insufficiently inclusive of women and youth. Using a normative juridical and socio-historical approach, this study demonstrates that musyawarah as the core of legitimacy has shifted from endogenous, adat-based legitimacy grounded in mutual cooperation (gotong royong) toward fragile, vertically regulatory legitimacy. This shift has led to the erosion of local wisdom and the weakening of the BPD’s supervisory function. In fact, the maxim dar’u al-mafāsid requires musyawarah to operate as an ethical mechanism for preventing harm (such as corruption of village funds) and to serve as the primary filter in every village decision. These findings lead to recommendations for normative reconstruction and the revitalization of inclusive, transparent, and locally grounded deliberative musyawarah, so that the BPD can once again function effectively as a supervisory body and guardian of village harmony in accordance with the principles of good governance and maqāṣid al-sharī‘ah.